2011
DOI: 10.1620/tjem.224.281
|View full text |Cite
|
Sign up to set email alerts
|

Serum Resistin as a Novel Marker of Erythropoietin Resistance in Nondiabetic Patients on Hemodialysis

Abstract: The use of higher erythropoietin (EPO) doses is associated with an increased risk of an adverse outcome and increased mortality in patients with renal failure. Resistin is related to heart disease, and may contribute to an increased atherosclerotic risk. We hypothesized that a link between resistin and EPO responsiveness may exist. We therefore investigated the relationship between resistin and the EPO resistance index (ERI) in nondiabetic hemodialysis (HD) patients. Fifty-seven patients enrolled in the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(34 reference statements)
2
2
0
Order By: Relevance
“…Our study demonstrated that ERI values were from 2.26 to 32.61 IU/week (g/dL) –1 /kg, and the mean ERI value was (12.67 ± 6.17) IU/week (g/dL) –1 /kg. These results are consistent with data reported by other studies [16, 17]. …”
Section: Discussionsupporting
confidence: 94%
“…Our study demonstrated that ERI values were from 2.26 to 32.61 IU/week (g/dL) –1 /kg, and the mean ERI value was (12.67 ± 6.17) IU/week (g/dL) –1 /kg. These results are consistent with data reported by other studies [16, 17]. …”
Section: Discussionsupporting
confidence: 94%
“…Our current study showed that ERI values were from 8.02 to 13.72 U/kg/ week EPO/Hb g/dL, and the mean ERI value was (10.95 ± 1.56) U/kg/week EPO/Hb g/dL. These data are consistent with data reported by other studies (3,19).…”
Section: Discussionsupporting
confidence: 92%
“…Whether our the effects of EPO are due to changes in the adipokine profile in our system has not been investigated; studies have demonstrated that chronic EPO treatment results in increased levels of leptin 28 and resistin, 38 however our investigations are limited to an acute model of contractility and experimental hypoxia. Whether other animal models, such as the obese rat or eNOS deficient mouse, will provide further insight into the protective mechanisms of EPO on vascular contractility remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%